Socializing Alone: How Online Homophily Has Underminded Social Cohesion in the US - Ruben Enikolopov; Maria Petrova; Gianluca Russo; David Yanagizawa-Drott (CESifo GmbH, 2024)
We examine the long-run effect of homophily in online social networks on interpersonal interactions in local communities. We measure online homophily across counties in the US using Facebook data. For identification, we exploit a conflict between Facebook and Google over data sharing of user information during the early expansion phase of Facebook. We find evidence that homophilic connections led to increased social media usage but reduced offline socialization. This shift was accompanied by deterioration of local social cohesion, as individuals became less connected across income strata and less likely to share the same political opinions with others in their counties.
Keywords: 330; social media; networks; homophily; social capital